Family power structure and identity styles in delinquent and nondelinquent Adolescents: A Comparative study in Tehran - Anahita Khodabakhshi Koolaee; Hossein Shaghlani Lor; Masoumeh Rahmatizade; Lesley Pocock (Shahid Beheshti University of Medical Sciences, 2016)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--> Background: The present study was conducted to investigate the Family Power Structure (FPS) and identity style in delinquent and non-delinquent juveniles in Tehran. Methods: To accomplish the goal of the study, 80 adolescent delinquents of the Correction and Rehabilitation Centers, aged between 15 and 18, were selected following cluster sampling procedure as well as 80 students of secondary school, aged between 15 and 18, in Tehran in 2014. To obtain data, FPS (Saidian, 2004) and Identity Style Inventory (ISI-6G: White et al, 1998) instruments were used. Data was analyzed between these two groups using independent t test, and Chi square test. Results: The findings indicated that there is a significant difference between delinquent and non-delinquent juveniles in FPS and its subscales (P<0.001) and identity style (P<0.001). Moreover, the informational identity style was related to lower levels of delinquency. In addition, a diffuse-evident identity style was found to be related to the delinquency. Conclusion: These findings emphasize that an inappropriate decision-making process pattern in a family has a significant effect on deviant behavior and identity style in adolescents. So, family counselors must pay attention to FPS in the therapeutic interventions (prevention and treatment) for adolescent delinquency. Keywords: Parenting; Family; Juvenile Delinquency; Adolescent <!--[if gte mso 9]> <w:LsdException Locked="false" SemiHidden="true" U